The importance of the Qinghai-Tibet Plateau for Bar-headed Geese Anser indicus: results from GPS/GSM telemetry - Zhang, Junjian; Deng, Xueqin; Xie, Yanbo; Li, Laixing; Batbayar, Nyambayar; Damba, Iderbat; Meng, Fanjuan; Cao, Lei; Fox, Anthony D. (Wildfowl, 2020)
The Bar-headed Goose Anser indicus is confined to central Asia, where it is currently increasing in abundance. Historically, the species has been divided into seven flyway units, of which the Eastern Flyway comprises 70% of the total world population. We used data from GPS-GSM transmitters deployed on Eastern Flyway Bar-headed Geese to differentiate between sub-populations exhibiting contrasting migration strategies and to assess the importance of the Qinghai-Tibet Plateau (QTP) for these sub-populations. Tracking results identified three distinctive sub-populations with differing migration patterns within the flyway. These were: 1) the Qinghai Lake–Shigatse Prefecture sub-population, short-distance migrants; 2) the Mongolia–Shigatse Prefecture sub-population, middle-distance migrants; and 3) the Mongolia–India/Bangladesh sub-population, long-distance migrants. Individuals in the short-distance sub-population remained in the QTP throughout their annual cycle. The middle-distance sub-population also exploited the QTP but returned north to Mongolia to breed. Geese from the long-distance sub-population departed their Mongolian breeding grounds early and spent > 80% of the total migration duration within QTP, despite this area constituting less than half the total migration distance during both autumn and spring migration. These results show that birds from all three sub-populations have a particular affinity for the QTP, confirming the importance of this area to all sub-populations of Eastern Flyway Bar-headed Geese. Migration among birds from the long-distance sub-population was significantly faster in spring than in autumn, the result using of fewer stopover sites and a shorter total stopover duration. We recommend more telemetry studies to confirm these patterns and support improved protection of site networks. Further ground surveys of Bar-head Goose numbers are also required, to identify threats to staging and wintering areas used by the different sub-populations of Bar-headed Geese in Eastern Flyway, with a view to securing key sites for the future.